Effect of long-term storage on the quality of cryopreserved sperm of the Pangasius nasutus (Bleeker, 1863) - Nurizzati Idris; Donald Torsabo; Muhammad Yazed Abduh; Ambok Bolong Abol-Munafi; Noordiyana Mat Noordin; Ivan Chong Chu Koh (Elsevier Inc, 2025)
In the present study, we investigated the effects of storage for 3, 6, 9 and 12 months on cryopreserved sperm of P. nasutus, in 10 % MeOH as a cryoprotectant with 90 % 0.9 % NaCl as an extender. Sperm quality on motility, fertilization, hatching, and deformity rates were investigated using 9-months cryopreserved sperm. Determine- Tion on the effects of different sperm to egg ratios also was evaluated using 1-year cryopreserved sperm. Post- thaw motility (PTM) of cryopreserved sperm within storage period was significantly lower compared to the initial motility of fresh sperm (51.67 ± 2.4 %). However, there was no significant change of PTM during 12 months of storage (3 months, 33.3 ± 2.33 %; 6 months, 32.0 ± 2.52; 9 months, 32.67 ± 1.76; 12 months, 33.33 ± 1.67). In addition, the motility duration was unaffected by storage as there was no significant difference compared to fresh samples. Besides that, there were no significant differences in motility, fertilization and deformity rates for fresh and 9-months cryopreserved sperm except for hatching rate. Samples stored for 1 year resulted in high fertilization across all sperm to egg ratios, showing no difference compared to fresh sperm. Cryopreserved sperm exhibited a significant higher hatching rate (9.24 ± 4.68 %) at the sperm to egg ratio of 300,000:1 compared to 150,000:1 (3.44 ± 1.7 %). However, no significant difference in deformity rates for fresh and cryopreserved at sperm to egg ratio of 300,000:1. The newly developed cryopreservation protocol using methanol successfully preserved sperm quality, maintaining fertilization rates comparable to fresh sperm. This highlights its potential application in sustainable aquaculture and conservation strategies for Pangasius nasutus.